(NwOPROSY SOWREMENNOJ MUZYKIs - (Nm(B.(Ns(B.(NdRUSKINs (NGLAWNYJ REDAKTORs ((NmOSKWAs (NlENINGRADs, 1963)
(NaWTORY STATEJ NASTOQ]EGO SBORNIKA(B-(NPROFESSORA(B,(NDOCENTY(B, (NPREPODOWATELI kONSERWATORII(B.s
Keywords: (NISTORIQs